EXPERIMENTAL STUDY OF THE PATHOGENICITY OF SHEEP AND BUFFALO ISOLATES OF FASCIOLA GIGANTICA IN GOATS - M. Al-Darraji‎, A.; I. Altaif‎, K.; Y.‎ Al-Kubaisee‎, R. (The Iraqi Journal of Veterinary Medicine, 1987)
In an experiment designed to study the pathogenicity of two isolates of F. gigantica, one of sheep and the other of buffalo origin, twenty-one, 3- months old goats were divided into 3 equal groups. The first received 5 metacercariae per kg body weight of the sheep strain and the second group has given the same dose of buffalo strain, while the third group was left as control. The main pathological findings were characterized as: fibrinous. perihepatitis, haemorrhagic tracts, haematomas, focal necrosis, hydroperitoneum and in the chronic phase by fibrosis and the typical pipe-stem liver. In animals of the second group, lesions were minor and consisted only of fewer heemorrhagic foci. The possible explanation of the difference in pathogenicity is discussed.